Hyperaldosteronism in children and adolescents - V. V. Smirnov; L. I. Bikbaeva (Лечащий Врач, 2021)
The review article considers current data on the etiology, pathogenesis, clinical picture, genetic diagnostics of hyperaldosteronism in children and adolescents. Phenotypic signs characteristic of this syndrome are described. Diagnostic methods and treatment strategies are presented.